2013
DOI: 10.1039/c3cp50367d
|View full text |Cite
|
Sign up to set email alerts
|

On the sensitivity of hard X-ray spectroscopies to the chemical state of Br

Abstract: The sensitivity of the 1s X-ray emission and high-energy-resolution fluorescence-detected X-ray absorption spectroscopies (XES and HERFD-XAS) to resolve the variations of the chemical state (electronic structure and local coordination) of Br has been investigated for a selected set of compounds including NaBrO 3 , NH 4 Br and C 2 H 4 Br 2 (1,2-dibromoethane). For the Br K-edge XAS, employing the HERFD mode significantly increases the energy resolution, which demonstrates that with a crystal spectrometer used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 103 publications
1
11
0
Order By: Relevance
“…In particular, the Br K-edge has been reported to be very sensitive to and undergo significant edge shifts depending on its environment, even without a change of the oxidation state. [72][73][74] The appearance of the 1s-4p resonance at 13.475 keV and the estimated oxidation shift of ~5 eV both point to a full positive charge localizing at the Br centres, by analogy with case of photoexcited aqueous Br -. 68 Charge localization may be caused by small hole polaron formation either at a defect or at a regular site of the lattice.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In particular, the Br K-edge has been reported to be very sensitive to and undergo significant edge shifts depending on its environment, even without a change of the oxidation state. [72][73][74] The appearance of the 1s-4p resonance at 13.475 keV and the estimated oxidation shift of ~5 eV both point to a full positive charge localizing at the Br centres, by analogy with case of photoexcited aqueous Br -. 68 Charge localization may be caused by small hole polaron formation either at a defect or at a regular site of the lattice.…”
Section: Discussionmentioning
confidence: 86%
“…The analysis of the spectra in Ref. 71 was carried out by simulating the density of states in order to reproduce the spectra. It was concluded that the pre-edge feature at 13.032 keV is dominated by the Pb p-orbitals, but it arises in the L 3 -edge spectrum due to their strong mixing with Pb d-orbitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, 'site-selective' crystal analyser spectrometers (Proux et al, 2017) can be used to improve the signal-to-background ratio and reveal spectral features that were invisible to conventional XANES. This high-energy resolution fluorescence detection (HERFD)-XAS has been successfully applied to better detect absorbing atoms (Co, Br, lanthanides) present in different oxidation states or different sites, in metallic oxides, minerals and even hightemperature supercritical fluids (Bordage et al, 2013;Hamalainen et al, 1991;Proux et al, 2017;Vitova et al, 2013). In the present study, HERFD-XAS has been used to investigate Br speciation in natural volcanic glasses.…”
Section: Introductionmentioning
confidence: 96%